Steelmaking technology and energy prices: The case of Germany - Anthony Britto; Emil Kraft; Joris Dehler-Holland (Karlsruhe Institute of Technology (KIT), Institute for Industrial Production (IIP), 2022)
We examine the relationship between the choice of steelmaking technology and energy prices in Germany using data beginning 1970. The analysis indicates that technology choice began to cointegrate with comparative energy prices in the early 90s. The short and long-run effects of energy prices are captured in a partial adjustment model; the ratio of electricity to coal prices is seen to exert sizeable influence on the short and long-term deployment of the electric arc furnace for secondary steelmaking. If current trends in energy prices continue, the share of secondary steelmaking in total steel production is expected to increase rather slowly.
Keywords: D24; O14; O33; Q49; C22; 330; technology adoption and diffusion; steelmaking; electric arc furnace; comparative energy prices; ARDL model